Echocardiographic evaluation of healthy cats under the effect of Dexmedetomidine and Butorphanol - L.I. Pereira; M.C.R. Milano; C.H. Oliveira; A.M. Amude; A.K. Fabretti; D.A.G. Kemper (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The study aimed to evaluate the applicability of the association of two classes of drugs. Ten healthy cats were used, who underwent echocardiographic evaluation and measurement of systemic blood pressure at baseline and after administration of dexmedetomidine at a dose of (10 mcg/kg) and butorphanol at a dose of (0.4mg/kg) intramuscularly. In the results obtained, there was a 12% decrease in free wall thickness in diastole in M mode (p=0.017), in addition to a 47% decrease in heart rate (p< 0.0001) and a 30% increase in systemic blood pressure (p<0.0001) after sedation. The TEI index increased (p<0.0001) and there was a significant impact on the systolic function of sedated cats, with a decrease in shortening fraction (p<0.0001), cardiac output (p = 20.003), S' wave (p = 0.007) and increased left ventricular diameter in M-mode systole (p = 0.0003). And the maximum velocities of the aorta (p = 0.015) and pulmonary artery (p < 0.0001) flows decreased, in addition to promoting alterations compatible with pulmonary artery hypertension. The association promotes sedation, but decreases systolic function, cardiac output and heart rate and increases afterload, therefore it is not suitable for echocardiographic evaluation.